GLP1R Attenuates Sympathetic Response to High Glucose via Carotid Body Inhibition. Issue 5 (1st February 2022) - Pauza, Audrys G.; Thakkar, Pratik; Tasic, Tatjana; Felippe, Igor; Bishop, Paul; Greenwood, Michael P.; Rysevaite-Kyguoliene, Kristina; Ast, Julia; Broichhagen, Johannes; Hodson, David J.; Salgado, Helio C.; Pauza, Dainius H.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Aberrant sympathetic nerve activity exacerbates cardiovascular risk in hypertension and diabetes, which are common comorbidities, yet clinically sympathetic nerve activity remains poorly controlled. The hypertensive diabetic state is associated with increased reflex sensitivity and tonic drive from the peripheral chemoreceptors, the cause of which is unknown. We have previously shown hypertension to be critically dependent on the carotid body (CB) input in spontaneously hypertensive rat, a model that also exhibits a number of diabetic traits. CB overstimulation by insulin and leptin has been similarly implicated in the development of increased sympathetic nerve activity in metabolic syndrome and obesity. Thus, we hypothesized that in hypertensive diabetic state (spontaneously hypertensive rat), the CB is sensitized by altered metabolic signaling causing excessive sympathetic activity levels and dysfunctional reflex regulation. Methods: Using a hypothesis-free RNA-seq approach, we investigated potential molecular targets implicated in energy metabolism mediating CB sensitization and its regulation of sympathetic outflow in experimental hypertension. Identified targets were characterized using molecular and functional techniques assessing peripheral chemoreflex sensitivity in situ and in vivo. Results: We discovered GLP1R (glucagon-like peptide-1 receptor) expression in the CBs of rat and human and showed that its decreased expression is linked to sympathetic hyperactivity in rats with cardiometabolic disease. We demonstrate GLP1R to be localized to CB chemosensory cells, while targeted administration of GLP1R agonist to the CB lowered its basal discharge and attenuated chemoreflex-evoked blood pressure and sympathetic responses. Importantly, hyperglycemia-induced peripheral chemoreflex sensitization and associated basal sympathetic overactivity were abolished by GLP1R activation in the CB suggesting a role in a homeostatic response to high blood glucose. Conclusions: We show that GLP1 (glucagon-like peptide-1) modulates the peripheral chemoreflex acting on the CB, supporting this organ as a multimodal receptor. Our findings pinpoint CBs as potential targets for ameliorating excessive sympathetic activity using GLP1R agonists in the hypertensive-diabetic condition.